2015
DOI: 10.3402/meo.v20.28796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical simulation training improves the clinical performance of Chinese medical students

Abstract: BackgroundModern medical education promotes medical students’ clinical operating capacity rather than the mastery of theoretical knowledge. To accomplish this objective, clinical skill training using various simulations was introduced into medical education to cultivate creativity and develop the practical ability of students. However, quantitative analysis of the efficiency of clinical skill training with simulations is lacking.MethodsIn the present study, we compared the mean scores of medical students (Jina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
(13 reference statements)
0
22
0
Order By: Relevance
“…Traditional didactic methods of teaching are insufficient in achieving the desired learning outcomes about the management of emergencies. Only clinical exposure to the medical emergencies can render adequate training on management of acutely ill patients, which is easily addressed by simulation, which may fill a gap in the current undergraduate medical curricula (6,17,18). Studies conducted previously among medical students have found that students value simulation-based learning highly (4,9).…”
Section: Data Collectionmentioning
confidence: 99%
“…Traditional didactic methods of teaching are insufficient in achieving the desired learning outcomes about the management of emergencies. Only clinical exposure to the medical emergencies can render adequate training on management of acutely ill patients, which is easily addressed by simulation, which may fill a gap in the current undergraduate medical curricula (6,17,18). Studies conducted previously among medical students have found that students value simulation-based learning highly (4,9).…”
Section: Data Collectionmentioning
confidence: 99%
“…Therefore, this study is in accordance with translational medicine concepts and, simultaneously, considers patient safety. All alterations of the teaching approach sufficiently mobilized medical students' productive thinking and study interests and increased the interactivity and communication between teachers and students (Zhang, Cheng, Xu, Luo, & Yang, 2015) This research has developed an innovative didactic teaching approach combining medical or virtual simulation and clinical practice-based interactive teaching and learning in a diagnostics and internal medicine curriculum based on translational medicine and patient safety concepts. The study has emphasized the close integration between clinical theory and practice.…”
Section: Value Of Constructing New Didactics In Internal Medicine Basmentioning
confidence: 99%
“…In China, history taking is taught in the fifth or sixth semester of education for a 5-year or 6-year clinical medicine major (Zhang, Cheng, Xu, Luo, & Yang, 2015;Pan, Cheng, Zhou, Li, & Yang, 2016). The current method of teaching history taking in Chinese medical schools mainly includes two parts: theoretical study and bedside practice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various teaching methods are introduced to teach students to take a complete medical history. These methods include lectures, using simulated patients, engaging in role-play activity and using videotape to record students' interviews (Keifenheim et al, 2015;Yu et al, 2017).In China, history taking is taught in the fifth or sixth semester of education for a 5-year or 6-year clinical medicine major (Zhang, Cheng, Xu, Luo, & Yang, 2015;Pan, Cheng, Zhou, Li, & Yang, 2016). The current method of teaching history taking in Chinese medical schools mainly includes two parts: theoretical study and bedside practice.…”
mentioning
confidence: 99%